Improving Police and Media Relations ir Serbia - Kešetović, Želimir (Sociologija. Mintis ir veiksmas, 2007)
In the introduction author underlines the utmost importance of good relations between the police and the community. As social reality in contemporary world is predominantly constructed by the mass media, they also play very important role in public perception of the police and in creating its image. On the other hand, the police is in the focus of media attention due to the fact that we live in “risk society”, where people are rather concerned for their safety and security. In that context mutual relations are important both for the police and the media. However, there are some general and universal problems that emerge in police-media relations due to structural factors that shape both professions. Author describes police and media relations during the system of personal rule that existed in Serbia during (1989-2000), in which the freedom of the press was seriously endangered, and the police was responsible only to the ruling elite. The police used mass media that were under the direct influence of the ruling party as their loud speakers, while the independent media were discriminated against and, from time to time, openly censored. Communications between police and the media were unilateral and one-way, while the public were treated as an object of influence. After the democratic changes in October 2000, the new democratic government launched extensive reforms in an attempt to establish rule of law and democratic institutions. As the police was one of the main pillars of the non-democratic regime, its reform was of utmost importance. In the context of overall reforms to make a shift from police force to police service, it was also necessary to change police-media relations. The tempo and results of the reform process was rather fast until the assassination of Prime Minister Zoran Đinđić in March 2002. Later on the process underwent a backlash, due to the new political conditions. With Organization for Security and Co-operation in Europe–OSCE, as a strategic partner, the project of improving police-media relations was launched in 2005. The first phase of the project included assessment of contemporary media and police relations in Serbia through a series of roundtable discussions organized in various regions of the country. Major findings of the actual problems in these relations, from the viewpoint of the journalist and police officers, are presented in the paper, as well as some system obstacles and recommendations for further improvement.